The Influence of Return on Assets (ROA) and Debt to Equity Ratio (DER) on Firm Value at PT. Indosat Tbk for the 2014-2023 Period - Nawawi, Nawawi (CV. Civiliza Publishing, 2025)
The sustainability of a company depends on the effectiveness of financial management, particularly profitability and capital structure. Return on Assets (ROA) measures a company's efficiency in generating profit from its assets, while the Debt to Equity Ratio (DER) indicates the balance between equity and debt. The balance between these two factors plays a crucial role in financial stability and the company's competitiveness. This study aims to determine the effect of Return on Assets (ROA) and Debt to Equity Ratio (DER) on firm value, both partially and simultaneously. The research sample consists of PT Indosat Tbk’s financial reports for the 2014-2023 period, using a saturated sampling method. This study employs a descriptive quantitative research method. The analytical method used is multiple linear regression analysis. The results indicate that, partially, ROA has no significant effect on firm value, and DER also has no significant effect on firm value. Simultaneously, ROA and DER do not have a significant effect on firm value.